Virtual Fossils from 425 Million-year-old Volcanic Ash - Briggs, D; Siveter, D; Siveter, D; Sutton, MD (2008)
The first major diversification of animal life took place during what paleontologists and evolutionary biologists refer to as the Cambrian Explosion. Deeper burrowers appeared in abundance during the succeeding period, the Ordovician, at which point buried carcasses became more vulnerable to scavenging. The Herefordshire fossils were deposited 425 million years ago within a marine basin that extended across what is now central England into Wales. The volcanic ash that engulfed the animals was deposited on top of a thin layer of mud covering thick limestones, the remnants of a reef that was effectively dead and had probably sunk well beneath the waves. The calcite casts proved too small and delicate to be dug out physically, and they could not be dissolved out chemically because they are so similar in composition to the rest of the concretion.